VIONE: Using Medication Optimization Techniques to Help Veterans Affairs Medical Centers Plan to Stop Taking Non-Essential Drugs - Saraswathy Battar (Internal Medicine, 2025)
In addition, patients often do not adhere to medication schedules due to side effects, compromised abilities to manage medication schedules, confusion, or cost.